2015
DOI: 10.1021/nl504662b
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Driven Reversible Insulator–Metal Phase Transition in 1T-TaS2

Abstract: In this work, we demonstrate abrupt, reversible switching of resistance in 1T-TaS2 using dc and pulsed sources, corresponding to an insulator-metal transition between the insulating Mott and equilibrium metallic states. This transition occurs at a constant critical resistivity of 7 mohm-cm regardless of temperature or bias conditions and the transition time is significantly smaller than abrupt transitions by avalanche breakdown in other small gap Mott insulating materials. Furthermore, this critical resistivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
186
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(192 citation statements)
references
References 20 publications
4
186
2
Order By: Relevance
“…the in-plane field can suppress CCDW distortion as well. The suppressions of CCDW by the in-plane field are usually explained as electron injection effect [23,26]. However, according to our calculation, CCDW could be stable upon electron doping.…”
Section: Resultsmentioning
confidence: 55%
See 2 more Smart Citations
“…the in-plane field can suppress CCDW distortion as well. The suppressions of CCDW by the in-plane field are usually explained as electron injection effect [23,26]. However, according to our calculation, CCDW could be stable upon electron doping.…”
Section: Resultsmentioning
confidence: 55%
“…To demonstrate the pure electron doping effect on CDW, more direct doping experiments by negative perpendicular electric field or liquid-gated method should perform. Some works reported the suppression of CCDW by in-plane electric field [22][23][24][25][26]. By measuring the temperature dependence of resistivity (R − T ), Yoshida et al found the in-plane field cannot affect the NCCDW/ICCDW transition in R − T curve, but can introduce a metastable state with very low resistivity at low temperatures [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastable phases of a CDW system are generally more susceptible to electronic perturbations, because CDWs directly couple to electric field (6)(7)(8)17). In our device, we observe that continuous current flow stabilizes the NC phase at low temperatures.…”
Section: Significancementioning
confidence: 99%
“…For device applications, it is desirable to control these phases by electrical means, but this capability is difficult to achieve in bulk crystals due to the high conduction electron density. Recent efforts to produce thin samples by mechanical exfoliation provide a new avenue for manipulating the CDWs in 1T-TaS 2 (4)(5)(6)(7)(8). These studies have demonstrated the suppression of CDW phase transitions using polar electrolytes, as well as resistive switching between the different phases.…”
mentioning
confidence: 99%